In Vitro Antioxidant Potential of Tuberous Root of Methanolic Extract of Ipomoea Digitata (Linn.) - G.ALAGUMANI VASAGAM; A.KOTTAI MUTHU; R.MANAVALAN (International Journal of Pharma and Bio Sciences, 2010)
In vitro antioxidant activities of methanol extract of tuberous root of Ipomoea digitata (Linn.) was investigated. The free radical scavenging activity to evaluate by Hydroxyl radical scavenging activity, FRAP method and Estimation of total phenol. Hydroxyl radical scavenging activity of methanolic extract and reference standard Ascorbate IC50 values was found to be 230 mg/ml and 410 mg/ml. FRAP method of methanolic extract and reference standard Ascorbate IC50 values was found to be 800 mg/ml and 50 mg/ml.The total phenol content of methanolic extract was found to be 7.51mg/g respectively. The above result possess significant antioxidant activity when compare to the above all standard.